ANALYSIS OF COPYRIGHT PROTECTION OF THE SERAM-PANG DUA BELAS DANCE REGIONAL ART AT THE DE-PARTMENT OF CULTURE AND TOURISM NORTH SUMATRA PROVINCE - Rahmadany, Rahmadany; Lubis, Anto Mutriady; Sriqodarsih, Chichi; Assiddiq, Muhammad Rafli; Laoly, Julia Morgan (Law Jurnal, 2026)
Copyright is right exclusive the creator who arises in a way automatic based on principle declarative after something creation realized in form real without reduce restrictions in accordance with provision regulation legislation . In its considerations , UUHC was born because Indonesia is a country that has diversity ethnicity / tribe and culture as well as wealth in the field art and literature with its development is necessary Copyright protection against riches born intellectual from diversity The art of dance needs to be protected to preserve cultural heritage, in the protection of Copyright and as an expression of traditional culture in Communal Intellectual Property. The Serampang Dua Belas Dance was created by Guru Sauti , but this dance considered represent art North Sumatra so government need protect it through scheme registration riches intellectual communal . Urgency study is Government quick register the Serampang Dua Belas Dance through scheme registration riches intellectual communal . This is important done For avoid claims of foreign countries , because Malaysia once claim art North Sumatra region, namely gondang part-time . This IPR registration is one of the efforts made government For lift the popularity of the Serampang Dua Belas Dance level national and international , registered to UNESCO as inheritance culture not object owned by Indonesia. Research objectives protect inheritance culture as form nationalism through method registration riches intellectual communal and inventory inheritance culture in form monograph . Monograph inheritance Indonesian culture , can inventoried . Research This support the RPJMN program , namely Asta goal 8, regarding strengthen alignment harmonious life with Indonesian culture . RIRN 2017-2045 focuses on encouraging development science and technology and economics as innovation inclusive for national development , which also includes Aspects of cultural development . Research methods is study through an empirical normative approach by taking qualitative data using descriptive methods , the results study This can made into input to the North Sumatra government to protect art area , so that more known at the level national and international and prevent claim from foreign countries . External study This Journal of LAW JOURNAL [ P-ISSN: 2746-4571 E-ISSN: 2746-3966]. Research results This using an empirical normative approach by collecting qualitative data. This was done so that the regional arts of North Sumatra could be protected and documented . inheritance culture nation this is very important , because 3 reasons , namely (1) the existence of potential profit economic results generated from utilization knowledge traditional , (2) justice in system world trade , and (3) the need for it protection right public local . Overcoming matter said , researchers do effort through activity Serampang Dua Belas Dance Performance about Importance Protection Wealth Intellectual The Serampang Dua Belas Dance Communal (KIK) was held at the Madani Hotel Medan and attended by the Research Team, Chancellor Unham , LPPM Unham , Students / I from several universities, Unham lecturers , school teachers, families Creator of the Serampang Dua Belas Dance , Owner Cipta Pesona Studio , Young Dancers Sanggar Cipta Pesona. Furthermore , to ensure that Indonesian Traditional Cultural Expressions (EBT) and works belonging to the Indonesian people are known to the international community, the Indonesian government has been protecting these works through claims by international cultural organizations. Researcher do effort create something Monograph For inventory inheritance culture nation as recommendation to government For protection inheritance culture nation as form nationalism nation . Preparation of the Procedure for the Regional Art Monograph of the Serampang Dua Belas Dance from the results of research activities through Field Visits to related agencies and selected History Museums & Dance Studios as well as Serampang Dua Belas Dance Art Performances and Research FGDs as well as research activities in data collection.